A conceptual framework for cooperation in hinterland development between neighbouring seaport authorities. Issue 6 (18th August 2018) - Hintjens, Joost
ABSTRACT: The hinterland of a port is probably the most important aspect in the competition between gateway ports. This paper, starting with a literature overview, shows how the port authority can extend its hinterland with the aim of increasing its attractiveness and, eventually, its throughput. To achieve this, it can be advantageous to cooperate with adjacent port authorities. Together, through cooperation, economies of scale can be realised that facilitate a modal shift away from road to a more efficient and more sustainable transport. This would reduce the cost of transport to/from the hinterland region from/to these ports consequently increasing the attractiveness and the market share of the cooperating ports for this region. The paper describes a conceptual method to identify and quantify the opportunities for cooperation in the hinterland. The framework starts, after some basic transport economic concepts, from (theoretically available) hinterland data to locate regions that are at the edge of the contested hinterland of a port region and results in a methodology that can be used to generate a quantified list of regions where cooperation will make a difference. Using this methodology, port authorities (PAs), of any region where hinterland data are available, can list, together with their neighbours, the regions where to prioritise their efforts.